Despindo o estratagema das políticas de desenvolvimento territorial no alto sertão sergipano : o (des)mascaramento da territorialização do capital por meio da sociabilidade reificante - Lima, Lucas Gama (2010)
The (re)planning is the keynote of the existing public policies. Since the late 1990s with the growing challenges of the limits of development guided by the local, mainly by restrictions on activities relevant to them, the scalar rhetoric gradually leaned to design the so-called "development track territory." According to its champions the uniqueness of this model is the combination of the elements of cohesion, as recommended by local development (cultural identity and strengthening of the civil society), with the ability to extend further promoted by the territorial development (because it extrapolates the municipal jurisdiction, bringing other municipalities). Among the benefits mentioned repeatedly by adopting this new model are: return of State investment, strengthening decision-making power of citizens, articulated relationship between the so-called actors of a determinate territory and, economic growth associated with improvement on the quality of life. The federal government since the year 2003 has sought to give expression to this proposed development with the creation of Secretariat for Territorial Development (SDT) and the creation of Rural Areas around the country. In Sergipe, pari passu with the general thrust of national policy for regional development, the State government since late 2006 has been promoting public policies for territorial approach, sometimes converging, sometimes diverging with initiatives of the federal government. This thesis has as main objective the intent to strip the "imposing" territorial development, highlighting the contradictions of their claims. These contradictions, far from justifying the operating order are settled in all the capital expansion. The same remains essentially due to the continuous production of surplus-values that can only be ensured with the formation of spatial arrangements and institutional compatible with its exploratory system. Thus, the State action, through a territorial development policy, is interfered with the social metabolism of the capital, since they are willing for their territorial areas and/or subordination in the name of development. To give legitimacy to this process are called the so-called "territorial actors" under fiery speeches that diffuse the possibility of social pact in an attempt to hide the object of irreconcilable differences between the classes by means of an abstract universality. The execution of the study revealed that the knowledge of the premises of territorial development boils down to the leaders of social movements and other entities participating in the Collegiate Place (so the gap between the discussions and deliberations of the body formally established by these representatives and their represented), and extent of development policy, disjointedly, reserve scarce resources for achieving the demands of collegiate authorities, at the same time when the State negotiates with the landlords and industrialists in another sphere, absolutely privileged. In this sense it is sought to capture in the thin lines of rhetoric escalate territorial development, as it is subsumed to the insatiable desires of the (re)production of capital, through the intervention of the State that preserves the reifying sociability.